2023
DOI: 10.3390/biom13040605
|View full text |Cite
|
Sign up to set email alerts
|

The N-Glycosylation of Total Plasma Proteins and IgG in Atrial Fibrillation

Abstract: Atrial fibrillation is a disease with a complex pathophysiology, whose occurrence and persistence are caused not only by aberrant electrical signaling in the heart, but by the development of a susceptible heart substrate. These changes, such as the accumulation of adipose tissue and interstitial fibrosis, are characterized by the presence of inflammation. N-glycans have shown great promise as biomarkers in different diseases, specifically those involving inflammatory changes. To assess the changes in the N-gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Although data on precise mechanistic pathways for diabetes mellitus (DM) remain limited, studies suggest that electrical and cardiac remodeling along with hyperglycemiainduced fibrotic change likely contribute to increased AF susceptibility. N-glycosylation involves the co-and post-translational addition of complex oligosaccharide structures (glycans) to proteins, influencing their structure, function, and processing, and are crucial for many biological processes, including cell signaling and recognition [26]. Recently, it has been shown that semaglutide, a glucagon-like peptide-1 receptor agonist that reduces the risk of adverse cardiovascular events in patients with diabetes, can lessen the cardiovascular risk associated with overweight and obese patients in the absence of diabetes as well [27].…”
Section: Early CV Diseases and Atrial Fibrillation In The Youngmentioning
confidence: 99%
“…Although data on precise mechanistic pathways for diabetes mellitus (DM) remain limited, studies suggest that electrical and cardiac remodeling along with hyperglycemiainduced fibrotic change likely contribute to increased AF susceptibility. N-glycosylation involves the co-and post-translational addition of complex oligosaccharide structures (glycans) to proteins, influencing their structure, function, and processing, and are crucial for many biological processes, including cell signaling and recognition [26]. Recently, it has been shown that semaglutide, a glucagon-like peptide-1 receptor agonist that reduces the risk of adverse cardiovascular events in patients with diabetes, can lessen the cardiovascular risk associated with overweight and obese patients in the absence of diabetes as well [27].…”
Section: Early CV Diseases and Atrial Fibrillation In The Youngmentioning
confidence: 99%
“…A recent study comparing 316 CAD-and 156 CAD+ patients revealed differences in IgG N-glycan composition, showing that sialylated N-glycan structures negatively correlate with CAD [183]. In addition, IgG N-glycans have shown potential as biomarkers for atrial fibrillation (AF), a condition resulting from both abnormal electrical signalling in the heart and a susceptible heart substrate [184]. Specifically, AF patients were found to have higher levels of plasma and IgG oligomannose and lower levels of IgG bisecting GlcNAc than controls.…”
Section: N-glycan Markers In Metabolic and Cardiovascular Diseasesmentioning
confidence: 99%
“…Additionally, glycans lacking core fucose have been reported to display pro-inflammatory effects, potentially triggering antibody-dependent cellular cytotoxicity [5]. The glycosylation of IgG changes based on physiological conditions, few examples being ageing [6], sex hormone influence [7], and changes in lifestyle factors such as changes in body weight [8] and pathophysiological states, including rheumatoid arthritis [9], diabetes [10], cancers [11], cardiovascular diseases [12], infectious diseases [13], among others. Glycans are highly stable within individuals (intraindividual stability), and the observed changes in pathological conditions make them potential candidates as diagnostic and prognostic biomarkers.…”
Section: Introductionmentioning
confidence: 99%